Attrition from Health Professional Schools in a Canadian University - Stewart, Miriam J. (Canadian Journal of Higher Education, 1990)
A descriptive study was conducted in order to identify the incidence of student voluntary withdrawal from undergraduate programs of the schools of the Faculty of Health Professions, in a Canadian university, over a two-year period; to identify students’ expressed reasons for voluntary withdrawal; and, to develop a profile of characteristics of students who withdraw voluntarily and those who are successful academically and continue/persist through to graduation. There were 30 respondents from among the 42 withdrawing students (73.2% response rate) and 85 respondents from among 120 eligible graduates sampled (70.8% response rate). Dropouts from the health professional schools in this Canadian university were typically older, married, and employed; considered their program less difficult; had not participated in orientation or contacted writers’ workshop, clubs, sports teams, student health, faculty advisors, or their profession’s clientele. These characteristics appear to reflect facets of academic integration more than social integration. Former students cited dissatisfaction with the program/curriculum content, uncertainty about educational/occupational goals, and stress associated with the profession as the three most important reasons for voluntary withdrawal.